PEMBUATAN LAPISAN TIPIS TiO2 PADA PLAT KACA DENGAN METODA DIP-COATING DAN UJI AKTIVITAS FOTOKATALISNYA PADA AIR GAMBUT - Sanjaya, Hary; Arief, Syukri; Alif, Admin (Jurnal Sainstek, 2013)
It Has been studied the preparation of Titania thin film on glass plate by dip-coating method and their photocatalityc activity test in peat swamp water. This study is performed by using TIP as precursor and DEA as aditive in isopropanol. The addition of DEA affect the stability of titania solution. The titania thin film was made by dip-coating method on glass plate. The glass plate was coated on to titania solution, then dryed at 110 C for 10 minute and at 500 C for 30 minute. The titania coating on the glass plate was made by varying the titania concentration : 0,5 M ; 0,75 M and 1,0 M. Analiyzing of the products by XRD shown that the titania coating on the glass plate are in anatase form. By visual analysis an photo optic, the best film on the glass plate that is coated with titania 0,5 M solution. Based on the glass plate that is coated with titania 1,0 M solution with peat swamp water shown relative good (68,26%) fot the irradiation during 24 hours.